Influences of arbuscular mycorrhizal fungi on Diospyros lotus seedlings under salinity stress - Meral Incesu; Berken Cimen; Bilge Yilmaz; Turgut Yesiloglu; Ibrahim Ortas (Frontiers in Plant Science, 2025)
Soil salinization, intensified by climate change, poses a growing threat to agricultural sustainability across the Mediterranean basin. As salinity levels rise in Mediterranean soils, the cultivation of salt-sensitive crops like persimmons is becoming increasingly vulnerable. This study investigated the effects of different arbuscular mycorrhizal fungi (AMF) species—Glomus clarium and Claroideoglomus etunicatum—on Diospyros lotus seedlings under varying salinity levels (0, 50, 100, and 150 mM NaCl). Seeds of D. lotus L. were used as a plant material, and the pot experiment was carried out under greenhouse conditions. Plant dry weight, chlorophyll, Fv/Fm, root colonization, and leaf and root mineral concentrations were investigated. Statistically, root colonization varied significantly with both mycorrhizal species and salinity levels, with C. etunicatum showing higher colonization rates than G. clarium across all treatments. Under saline conditions, both AMF species-inoculated plants exhibited significantly higher fresh and dry weights, chlorophyll content (SPAD), and photosystem II efficiency (Fv′/Fm′), and reduced symptom scores. C. etunicatum demonstrated superior tolerance to salinity, maintaining higher biomass and chlorophyll fluorescence at elevated salt concentrations. Mycorrhizal dependency values exceeded 70% under salinity, reflecting the critical role of AMF in enhancing stress resilience. It was determined that D. lotus seedlings are dependent on mycorrhiza and cannot grow in conditions without mycorrhiza inoculation. Mineral nutrient analysis revealed increased concentration of Ca, K, P, Mg, Fe, Mn, and Zn, and moderated Na and Cl accumulation in AMF-inoculated seedlings, with G. clarium particularly effective at limiting sodium translocation. These findings demonstrate that AMF inoculation, particularly with C. etunicatum, can effectively mitigate salinity-induced damage and improve nutrient balance, growth, and physiological performance in D. lotus. The results highlight the potential of mycorrhizal inoculation for sustainable cultivation in saline soil conditions.